PELATIHAN PEMBELAJARAN BAHASA INDONESIA BERBASIS KESANTUNAN BUDAYA SUNDA BERMEDIA AUDIO VISUAL - Tia Irawan; Dheni Harmaen (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2019)
This paper is motivated by the existence of an imbalance in the understanding of the Sundanese students of the Indonesian Language Education Study Program FKIP UNPAS in understanding statements or expressions that use regional languages. In contrast to their speed at understanding statements expressed in a foreign language, or Indonesian. In addition, in everyday life there are still many people who cannot speak the local language, and even seem afraid to use it. Moreover, with the increasing number of foreign terms used in daily activities, as well as the intensity of globalized communication, it is increasingly adding to the scarcity of the use of the regional language. Of course this is very ironic, because many people, including students, do not understand their own regional language, while foreign languages ​​or other second languages ​​are very quickly understood. The low interest of local language students, as well as the existence of different thoughts and treatments on the use of regional languages, as well as the lack of student understanding of regional languages ​​and cultures encourage writers to find a solution by utilizing existing conditions through learning local languages ​​based on local wisdom by utilizing audio-visual media. . Therefore, the authors feel the need to improve their abilities and attitudes, especially the students towards their own regional language. In order to improve students' ability to understand the local language, the author tries to provide a learning of regional language skills by raising the culture or habits according to local wisdom in their respective regions.The study was conducted in the learning of regional languages ​​with the aim of increasing the willingness and ability of students to preserve regional languages ​​and cultures. The research method that the author uses is to use the experimental method. This method is used to test the effectiveness of using Audio-Visual Media in learning local languages ​​by raising local wisdom. The research technique that the author uses is a test and questionnaire technique. The test is used to measure regional language skills productively (speaking and writing) by utilizing audio-visual media. While the questionnaire was used to determine the responses and attitudes of students towards learning and efforts to preserve local languages. By creating a creative and innovative learning, this research tries to provide a solution to answer the existing demands and needs. The results of this study are expected to be an effort in the preservation of regional languages, especially for students as the most important part in agents of change in the preservation of the regional language. With the packaging of regional language learning that elevates local wisdom through audio-visual media, it is hoped that students' love for the language and culture of their own region will be embedded. and international. For this reason, the author feels it is important to conduct this research as an effort to preserve the local language. Keywords: regional language, local culture, local wisdom, audio-visual media, willingness & ability.